2008
DOI: 10.1111/j.1461-0248.2008.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological consequences of genetic diversity

Abstract: Understanding the ecological consequences of biodiversity is a fundamental challenge. Research on a key component of biodiversity, genetic diversity, has traditionally focused on its importance in evolutionary processes, but classical studies in evolutionary biology, agronomy and conservation biology indicate that genetic diversity might also have important ecological effects. Our review of the literature reveals significant effects of genetic diversity on ecological processes such as primary productivity, pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,432
5
25

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,499 publications
(1,560 citation statements)
references
References 112 publications
36
1,432
5
25
Order By: Relevance
“…2017). It has been demonstrated that even small differences in genetic diversity (such as single amino acid substitutions) can yield large differences in chemical profiles (Kampranis et al., 2007), and several studies have found that higher intraspecific genetic diversity reduces herbivory and disease in plant populations (Hughes, Inouye, Johnson, Underwood, & Vellend, 2008). Moreover, emerging evidence has demonstrated how variation in intraspecific chemodiversity influences community diversity among different trophic interactions (Glassmire et al., 2016; Richards et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2017). It has been demonstrated that even small differences in genetic diversity (such as single amino acid substitutions) can yield large differences in chemical profiles (Kampranis et al., 2007), and several studies have found that higher intraspecific genetic diversity reduces herbivory and disease in plant populations (Hughes, Inouye, Johnson, Underwood, & Vellend, 2008). Moreover, emerging evidence has demonstrated how variation in intraspecific chemodiversity influences community diversity among different trophic interactions (Glassmire et al., 2016; Richards et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing genetic and phenotypic variations within a species typically increases species diversity and abundance and primary productivity, promotes positive plant–soil interactions (reviewed in Crutsinger, 2016), and stabilizes ecosystem functions (Genung et al., 2010; Prieto et al., 2015). Although species and individual interactions due to variance in individuals are less predictable, these effects appear to be strongest when the species in question plays an important role in the ecosystem (Hendry, 2016; Hughes, Inouye, Johnson, Underwood, & Vellend, 2008); that is, it is a “keystone species,” “foundation species,” “niche constructor,” “strong interactor,” and so on.…”
Section: Intraspecific Variation Is Critical For Population Dynamicsmentioning
confidence: 99%
“…Additional effects of lost genetic variation is the sublethal effects on ecosystem function that have been documented most comprehensively in cultured plants (Hughes et al 2008) but is observed also in populations of marine species. For example, decreased genetic variation in populations of barnacle larvae had a negative impact on larval recruitment (Gamfeldt et al 2005).…”
Section: Effects Of Genetic Variation On Ecosystem Functionmentioning
confidence: 99%